Plasma amyloid-beta levels and risk of new-onset atrial fibrillation in the general population. (3rd October 2022) - Lu, Z; Tilly, M; Wolters, F; De Groot, N M S; Ikram, M A; Kavousi, M
Abstract: Background: Atrial fibrillation (AF) is a major health burden worldwide, with significant sex differences in epidemiology and risk factors. Amyloid-β40 (Aβ40) and Amyloid-β42 (Aβ42), the hallmark of cerebral amyloid angiopathy, have recently been linked to prevalence and prognosis of several cardiovascular outcomes including stroke and coronary heart disease. However, whether these biomarkers are associated with incident AF remains largely unknown. Purpose: To investigate the associations between plasma concentrations of Aβ40 and Aβ42 with new-onset AF. Methods: 4, 134 participants without a history of AF at baseline (from 2002 to 2005) with qualified plasma samples in the Rotterdam Study were included in this study. AF was diagnosed by electrocardiograms, general practitioners' and hospital records. Cox proportional hazards regression models with natural cubic splines were used to assess the linear/nonlinear association between biomarkers and risk of new-onset AF. All models were adjusted for traditional cardiovascular risk factors. Results: Mean age was 71.3±7.2 years and 2, 383 (57.6%) were women. Median follow-up time was 9.2 years. In the fully adjusted model, higher levels of Aβ40 [hazard ratio, 95% confidence interval: 1.16 (1.05–1.28)] and Aβ42 [1.19 (1.09–1.31)], as well as Amyloid-β42 to β40 ratio (Aβ42/40) [1.09 (1.02–1.17)] were significantly associated with incident AF. The observed association between Aβ40 and AF attenuated after mutual adjustment for Aβ42 [1.05 (0.92–1.19)]. In addition, a J-shaped association was found between Aβ40 and AF with the lowest AF risk at Aβ40 values of 212.5 pg/ml. Conclusions: Both Aβ40 and Aβ42 were independently significantly associated with new-onset AF in the general population independent of cardiovascular risk factors. Findings also suggest a stronger association between AF onset and Aβ42 and AF onset, compared to Aβ40. A nonlinear association was found between Aβ40 and AF, reflecting a substantially increased AF risk among participants with severely increased Aβ40 values. Funding Acknowledgement: Type of funding sources: None.